Iran and Oman - Shamshiri-Fard, Marral (2020)
Keywords: Relations – Oman – Iran

Anticolonialism, Third Worldism, and the Cold War: Writing Transnational Decolonial Histories from Dhofar to Tehran - Shamshiri-Fard, Marral (2020)
Keywords: Relations – Oman – Iran

Challenging Empire in the Persian Gulf: Transnational Guerrilla Networks and Iranian Revolutionaries in Oman - Shamshiri-Fard, Marral (2020)
Keywords: Relations – Oman – Iran

Imperial Histories in the Arabian Peninsula: The Iranian Intervention in Oman (1972-1975) - Shamshiri-Fard, Marral (2020)
Keywords: Relations – Oman – Iran

Affective and Gendered Politics of Liberation: Anti-Imperialist Praxis and Solidarity with the Dhofar Revolution - Shamshiri-Fard, Marral (2020)
Institution: American Studies Association
Keywords: Relations – Oman – Iran

Oman. Comment le chah d'Iran a sauvé le régime - Une page d'histoire oubliée - Pellas, Marc (Orient XXI, 2020)
Décédé en janvier 2020, le sultan d’Oman Qabous Ibn Saïd avait livré au début de son règne, dans les années 1970, une guerre de plusieurs années contre les rebelles (...)
Keywords: Relations – Oman – Iran